2023
DOI: 10.1108/jhti-09-2022-0442
|View full text |Cite
|
Sign up to set email alerts
|

Activities as the critical link between motivation and destination choice in cultural tourism

Abstract: PurposeThis study aimed to determine the motivations of a select group of South Africans in terms of their potential engagement with cultural tourism; more specifically, the study set out to show whether these motivations influence the cultural activities that the tourists want to participate in and whether their interest in specific cultural activities determines their destination choices. Furthermore, the mediating role of activities in the relationship between cultural motivations and destination choice was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 89 publications
0
4
0
Order By: Relevance
“…While each destination does offer unique attractions (for example, the Sunshine Coast has the famous Australia Zoo, while the Gold Coast has four major theme parks), they act as facilitators and not magnets. This observation that destination attributes play little or no role in destination choice as suggested by Douglas et al (2023), Hanna and Rowley (2019) creates real challenges for Destination Management Organisations (DMOs). DMOs rely on effective branding and positioning to differentiate similar places in a meaningful way (Morgan & Pritchard, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While each destination does offer unique attractions (for example, the Sunshine Coast has the famous Australia Zoo, while the Gold Coast has four major theme parks), they act as facilitators and not magnets. This observation that destination attributes play little or no role in destination choice as suggested by Douglas et al (2023), Hanna and Rowley (2019) creates real challenges for Destination Management Organisations (DMOs). DMOs rely on effective branding and positioning to differentiate similar places in a meaningful way (Morgan & Pritchard, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Crompton's (1979) foundational work on motivations extended this list significantly by identifying nine dominant motives for travel. Other studies have essentially confirmed the ubiquity of these push factors (Douglas et al, 2023;Klenosky, 2002;Lee et al, 2002;Mutinda & Mayaka, 2012).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Since cultural distance may increase the level of uncertainty and risk faced by tourists in a foreign country, cultural similarity, on the other hand, can indicate the degree of comfort and familiarity tourists may experience (Liu, 2014). In this regard, tourists are more likely to select culturally similar countries as destinations, according to some studies (Mancini-Cross et al, 2009;Lo et al, 2011;Garamvölgyi & Rudnák, 2016;Douglas et al, 2023). Due to this, it is assumed that "Lack of cross-cultural risk control" might negatively affect "Traveller's risk tolerance".…”
Section: H2a: Lack Of Physical Risk Control Negatively Affects Travel...mentioning
confidence: 99%
“…In cultural tours, tourists perceive certain values in return for the service and experience they have consumed or will consume. Cultural tourists receive service from the tour guides accompanying them in the language they prefer while learning about the historical, artistic, environmental, natural, and cultural assets of the destinations and historical sites visited (Akgunduz & Eser, 2022;Douglas, Hoogendoorn, & Richards, 2023;Hwang & Lee, 2019;Latkova, Jordan, Vogt, Everette, & Aquino, 2020;Mousa, Abdelgaffar, Salem, Elbaz, & Chaouali, 2023;Weiler & Black, 2021). Tour guides shape the destination experiences of tourists, bringing value and meaning to the overall experience (Cheng, Kuo, Chang, & Chen, 2019;Huang, Hsu, & Chan, 2010;Nour Salah Al-Okaily Alzboun, & Abuhjeeleh, 2023) while impacting tourists' satisfaction levels and behavioral intentions (Chang, 2014;Cheng et al, 2019;Fu, Li, XU, Liu, & Chen, 2023;Huang et al, 2010;Zeng & Yi Man Li, 2021).…”
Section: Introductionmentioning
confidence: 99%